2013
DOI: 10.1088/1748-6041/8/4/045007
|View full text |Cite
|
Sign up to set email alerts
|

Structural changes in PVDF fibers due to electrospinning and its effect on biological function

Abstract: Polyvinylidine fluoride (PVDF) is being investigated as a potential scaffold for bone tissue engineering because of its proven biocompatibility and piezoelectric property, wherein it can generate electrical activity when mechanically deformed. In this study, PVDF scaffolds were prepared by electrospinning using different voltages (12-30 kV), evaluated for the presence of the piezoelectric β-crystal phase and its effect on biological function. Electrospun PVDF was compared with unprocessed/raw PVDF, films and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
127
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 166 publications
(131 citation statements)
references
References 34 publications
3
127
1
Order By: Relevance
“…Polyvinylidine fluoride (PVDF) (Damaraju, Wu, Jaffe, & Arinzeh, 2013) prepared by electrospinning at different voltages (12 and 25 kV) was compared to tissue culture polystyrene.…”
Section: The Need For Function: Mechano-electrical Stressmentioning
confidence: 99%
“…Polyvinylidine fluoride (PVDF) (Damaraju, Wu, Jaffe, & Arinzeh, 2013) prepared by electrospinning at different voltages (12 and 25 kV) was compared to tissue culture polystyrene.…”
Section: The Need For Function: Mechano-electrical Stressmentioning
confidence: 99%
“…Recently, poly (vinylidene) fluoride (PVDF) and its copolymer poly (vinylidene fluoride-trifluoroethylene) (PVDF-TrFE), both exhibiting piezoelectric characteristics, have been explored as potential scaffold materials for tissue engineering applications. Piezoelectric scaffolds possess the intrinsic property of producing an electrical voltage in response to mechanical deformation without the need for external power sources or electrodes (Damaraju et al, 2013;Lee and Arinzeh, 2012;Martins et al, 2013;Weber et al, 2010a). While the feasibility of PVDF-TrFE scaffolds for bone and neural cell studies have recently been demonstrated, the effect of PVDF-TrFE scaffolds on cardiovascular cells has not yet been explored.…”
Section: Introductionmentioning
confidence: 99%
“…2b) were fabricated via electrospinning with the BTO concentrations of 5, 10, 15 and 20 wt%. The FTIR [29][30][31][32] and XRD 29,31,33 studies of the BTO-PVDF mats are presented in Supplementary Note 1.…”
Section: Resultsmentioning
confidence: 99%